Atomic layer deposition of alumina onto yolk-shell FeS/MoS2 as universal anodes for Li/Na/K-Ion batteries. (10th January 2022) - Han, Bo; Chen, Shuangqiang; Guo, Chaofei; Wu, Minghong; Wang, Yong
Abstract: Transition metal sulfides are regarded as a category of promising electrodes for alkaline ion batteries because of their high theoretical capacities, fast ionic conductivity and low cost, but they also face many challenges on large volume changes, sluggish kinetics and instability of solid electrolyte interphase (SEI). To tackle these issues, this work designs iron sulfide/molybdenum disulfide (FeS / MoS2 ) yolk-shell sphere electrodes coated by few-nanometer thick alumina film. Such alumina film is adopted to minimize side reactions, promote the formation of stable SEI, and enhance the mechanical stability of the electrode. Specifically, when used as anode materials at 100 mA g −1 in Li/Na/K-ion batteries, the coated electrode (ALD-40-E) can deliver reversible capacities of 1007, 570 and 367 mAh g −1  after 100 cycles, respectively, which are substantially larger than those of bare FeS / MoS2 electrode (ALD-0-E: 538, 311 and 213 mAh g −1 ) and FeS / MoS2 with direct alumina coating on powder surface (ALD-40-P: 429, 116 and 86 mAh g −1 ). Good electrochemical properties are mainly ascribed to the yolk-shell structure, and the alumina thin film on the electrode, which work synergistically to maintain the electrical contact, facilitate the ion/electron diffusion paths, accommodate volume change and preserve structural stability.